Perlindungan Hukum Terhadap Konsumen Dalam Transaksi E-commerce - Zainudin Hasana; Icha Ifa Afifah (Advances In Social Humanities Research, 2023)
In this ever-evolving digital era, consumers can easily purchase goods and services online with just a few clicks. E-commerce transactions offer convenience and accessibility. However, consumers are often exposed to various risks such as product discrepancies, fraud, unauthorized disclosure of personal data, and injustice in dispute resolution. The purpose of this research is to discuss legal protection in e-commerce transactions for consumers. The results of this study are that the provisions in UUPK do not fully accommodate consumer rights in e- commerce transactions. This is because e-commerce has different characteristics from conventional transactions. Some of these characteristics include the absence of direct meetings between sellers and buyers, the use of internet media as a means of transaction, etc.